Integrating emergy accounting with ecosystem-based coastal defence: An eco-coastal engineering framework for sustainability assessment of hybrid infrastructure - Junxue Zhang; Moran Yu; Hairuo Wang; Yan Gong; Haobing Wang; Xiaoting Zhai; Ashish T. Asutosh; Yingnan Li; Ge Song; Weidong Wu; Ziyi Men; Minghui Yang; et al. (Ocean Engineering, 2026)

Aerobic biotransformation of 8:2 FTCA in activated sludge: Carbon source dependence and multiple transformation pathways - Xue-Ming Zhang; Chun-Yu Lai; Yujie Men; He-Ping Zhao (Journal of Hazardous Materials, 2026)

Reinforcing electrolyte skeleton via in-situ cross-link enhancement for solid-state lithium metal batteries - Ziwen Tian; Mohan Yang; Yutao Wang; Qiwei Wu; Yu Guan; Hao Men; Yali Li; Lian Wang; Yuefeng Su; Yong Zhao (Chemical Engineering Journal, 2026)

Spatiotemporal Patterns, Driving Mechanisms and Responses of Soil Drought to Meteorological Drought in the Yellow River Basin of China - Fei Wang; Wenhan Yu; Yi Zhang; Hexin Lai; Mengting Du; Qian Xu; Rong Li; Ruyi Men; Haoyu Li; Kai Feng; Shikai Gao; Yanbin Li; et al. (International Journal of Climatology, 2026)
With the escalation of global warming, the potential for land evaporation in the Yellow River Basin (YRB) has increased remarkably, and the problem of soil drought has become increasingly prominent. This not only restricts the development of the agricultural economy in the basin, but also intensifies the disparity between water availability and demand, and exerts a profound influence on the ecological security of the basin. In light of this, this study focuses on soil moisture in the YRB from 2000 to 2022, and conducts an in‐depth analysis of the temporal evolution, spatial patterns, abrupt change characteristics as well as the driving forces of soil drought by calculating the Standardised Soil Moisture Index (SSMI). The results show that: (1) Soil drought in the YRB from 2000 to 2022 exhibited a decreasing trend. A negative abrupt change point occurred in February 2004, indicating a sudden intensification of arid conditions. The soil drought in the Above Longyangxia (AL) region exhibited the most significant decreasing trend in September. (2) The most severe soil drought occurred in 2006, and the drought was most intense in November of that year, when the drought‐affected area reaching 86.96%. The severely drought‐stricken areas were predominantly concentrated in the central and northern regions of the basin. (3) The SSMI in the second‐level sub‐regions of the YRB exhibits three types of abrupt changes: increase to decrease, intermittent increase, and decrease to increase, and shows a clear trend from upstream to downstream. (4) The results of cross‐wavelet analysis indicate that soil moisture‐absolute humidity‐soil temperature is the best explanatory combination for soil drought. (5) The slopes of the small‐ and medium‐scale fittings in the AL region are 0.5021 and 0.2584, respectively, and the corresponding mean values of meteorological drought severity are 0.87 and 2.57, respectively. Drought events in the YRB are mainly of medium/short duration and low severity, and soil drought severity tends to increase with the intensification of meteorological drought. This study reveals the spatiotemporal variation patterns of soil drought in the YRB, as well as the responses of climate to soil drought. These findings provide a scientific basis for drought resistance and ecological protection within the basin.

Ship engine room pipe layout optimization based on a knowledge-driven sparse A∗ algorithm - Dechen Liu; Yanyun Yu; Hongshuo Zhang; Xiang Liu; Qi Men; Yan Lin (Ocean Engineering, 2026)

Inhibition of endothelial S1PR2 preserves blood-brain barrier integrity after traumatic brain injury through activating the PI3K-AKT signaling pathway - Hongbo Cheng; Qin Wang; Yijiao Men; Yaqing An; Botao Ma; Shimei Dai; Zhuang Jing; Xuerui He; Xiaoqing Bao; Yinbo Long; Jiegang Yu; Yang Wu; et al. (Molecular and Cellular Biochemistry, 2026)

Gut-muscle axis improves meat quality by regulating energy metabolism - Haoyu Liu; Lihang He; Ning Ma; Peng Tan; Qi Tang; Kun Cai; Zhaoyue Men; Yutong Lu; Dingyue Hu; Jinshan Zhao; Cunxi Nie; Shuyang Yu; et al. (Meat Science, 2026)

Sensitivity analysis and multi-objective particle swarm optimization (MOPSO) of a hollow fiber membrane module for the solar-based heating and humidification system - Si Zeng; Peng Peng; Nan-Feng Li; Cai-Hang Liang; Rong-Hui Qi; Yan-fang Dong; Yu-Kui Men; Jia-Hui Li; Gui-Yin Li (Energy and Buildings, 2026)

In situ polymerization-induced confined aggregation of poly(ionic liquid)-BiOBr nanosheets for enhanced photocatalytic activity - Li-Min Yu; Yong-Ya Zhang; Li-Jing Wang; Huan-Ning Li; Pan Li; Jia-Qi Men; Wei Wei; Shi-Jie Li (Environmental Research, 2026)

A hybrid AWQMIX-MGT algorithm integrating deep reinforcement learning and collaborative optimization strategies for ship equipment and pipe layout design - Hongshuo Zhang; Yanyun Yu; Qiang Li; Dechen Liu; Qi Men; Xiang Liu; Yan Lin (Ocean Engineering, 2026)

A method for assessing the odor intensity of polypropylene materials with an electronic nose to simulate a panel of olfactory sensory - Chengrui Yu; Yanwei Wang; Yudong Yan; Yan Shi; Yuxiang Ying; Hong Men (Chemical Engineering Journal, 2025)

Spatial optimization of Best Management Practices (BMPs) for nonpoint source pollution mitigation in agricultural watersheds - Yujiao Wu; Yu Li; Yiding Men; Zhe Zhu; Yan Sun; Changchun Song (Journal of Hydrology, 2025)

Soybean insoluble Fiber-EGCG binary compounds: Enhanced stability and synergistic antioxidant activity - Yi Wang; Ruining Zhang; Shidi Men; Mingzhe Li; Guannan Liu; Xiangbo Zeng; Bo Lyu; Sainan Wang; Hansong Yu (Food Chemistry, 2025)

Absolute configuration of unisolated epimers of pseurotin D from the marine-derived fungus Penicillium janczewskii - Yu Kyung Choi; Gyu Sung Lee; Yeongseo Kim; Men Thi Ngo; Jin Wook Cha; Chung Sub Kim; Kyo Bin Kang (Phytochemistry Letters, 2025)

Development and application of InDels and SNPs markers based on whole-genome resequencing in Chinese cabbage - Kai-Wen Liu; Wan-Jie Men; Jin-Xia Feng; Iqbal Hussain; Hui Sheng; Li-Wei Zhang; Zhong-Ren Dai; Hai-Jiang Hu; Jian-Hao Yang; Na Lei; Xiao-Lin Yu (Horticulture, Environment, and Biotechnology, 2025)

Reducing environment and enhanced productivity controlled the accumulation of organic matter in the Upper Yangtze Basin, South China during the Late Ordovician-Early Silurian - Yan-Jun Bao; Yuan-Yuan Sun; Di Zhang; Jian-Fei Yan; Yu-Peng Men; Wei Sun; Jia-Shan Lin; You-Li Wan; Jian-Wei Kang; Wen-Hua Wang; Qiangba Zhaxi (Journal of Asian Earth Sciences, 2025)

An optimized double-layer MXene/chitosan interfacial solar evaporator with reduced water evaporation enthalpy via channel size minimization - Jie He; Jiahui Xiao; Qinxing Zhang; Tonghua Men; Yu Wang; Xiaofeng Wang; Bo Wang; Chuntai Liu; Changyu Shen; Wenjuan Han (Chemical Engineering Journal, 2025)

Repair effects of melatonin application on physiological damages induced by UV-B radiation in alfalfa seedlings - Yongfeng Li; Haitao Men; Jiajia Li; Wenxia Cao; Yu Pan; Limei Gao (Protoplasma, 2025)

Catalytic reforming of leachate from food waste towards hydrogen generation and wastewater treatment - Yongjie Hu; Yueyang Dai; Qi Gao; Yingying Yu; Yincheng Wang; Beibei Yan; Yanhui Men; Junyu Tao; Guanyi Chen (Journal of Water Process Engineering, 2025)

Origin traceability of agricultural products: A lightweight collaborative neural network for spectral information processing - Yan Shi; Yang Yu; Jinyue Zhang; Chongbo Yin; Yizhou Chen; Hong Men (Food Research International, 2025)

Comparison of plastisphere microbiomes during the degradation of conventional and biodegradable mulching films - Hao Yu; Mingyang Zhang; Huiying Liu; Juanjuan Xiao; Jianan Men; Tomislav Cernava; Ye Deng; Decai Jin (Journal of Hazardous Materials, 2025)

ColorNet: An AI-based framework for pork freshness detection using a colorimetric sensor array - Guangzhi Wang; Yuchen Guo; Yang Yu; Yan Shi; Yuxiang Ying; Hong Men (Food Chemistry, 2025)

Regulatory role of exosomal proteins MIF and PEBP1 in sperm storage in black rockfish (Sebastes schlegelii) ovary - Ying Chen; Yu Men; Kai Yan; Wajid Ali; Zibin Li; Wenxiu Cai; Yan He; Jie Qi (Aquaculture, 2025)

Land-atmosphere feedback exacerbated the mega heatwave and drought over the Yangtze River Basin of China during summer 2022 - Xiao Chen; Jialin Wang; Feifei Pan; Yu Song; Ju Liang; Na Huang; Kang Jiang; Riping Gao; Jingyu Men; Pengshuai Bi; Fangxiao Zhang; Zhanrui Huang; et al. (Agricultural and Forest Meteorology, 2025)

Chromium contamination affects the fungal community and increases the complexity and stability of the network in long-term contaminated soils - Hao Yu; Qi Huang; Jianan Men; Jian Wang; Juanjuan Xiao; Decai Jin; Ye Deng (Environmental Research, 2024)

Regulation of sperm motility by exosomes of ovarian fluid during female sperm storage in black rockfish (Sebastes schlegelii) - Ying Chen; Xi Zhao; Yu Men; Kai Yan; Zibin Li; Wenxiu Cai; Yan He; Jie Qi (Aquaculture, 2024)

Pre-coagulation with novel titanium coagulants for mitigating membrane fouling in direct membrane filtration of municipal wastewater - Yu Men; Xuemei Wang; Shikun Cheng; Lixin Zhu; Zifu Li (Chemical Engineering Journal, 2024)

Assessment of the impact of Tianwan Nuclear Power Plant on the adjacent marine ecosystem - Yue Yu; Wu Men; Yaoyao Xu; Fenfen Wang (Marine Pollution Bulletin, 2024)

Assessment of radiation in fishes derived from radiocesium in the port of Fukushima Daiichi nuclear power plant - Yaoyao Xu; Wu Men; Yue Yu; Fenfen Wang (Marine Pollution Bulletin, 2024)

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Evaluation of the Pollination Efficiency of Apple Trees by Osmia excavata Alfken (Hymenoptera: Megachilidae) - Zhaoyun Lyu; Min Feng; Lei Nie; Ting Zhou; Kai Yu; Lili Li; Xingyuan Men; Meng Sun; Yi Yu (Neotropical Entomology, 2024)

Comparison of the flight ability of diapausing and post-diapause Osmia excavata Alfken (Hymenoptera: Megachilidae) at different temperatures - Zhaoyun Lyu; Haigang Liu; Ting Zhou; Min Feng; Zengbin Lu; Lei Nie; Guiping Wang; Guangzhao Wang; Lili Li; Xingyuan Men; Meng Sun; Yi Yu (Journal of Asia-Pacific Entomology, 2024)

Characterization of key flavor substances and their microbial sources in traditional sour bamboo shoots - Hui Tang; Jin-Kui Ma; Lin Chen; Li-Wen Jiang; Lin-Zhi Kang; Ying-Yu Guo; Ge-Yang Men; Dan-Xia Nie; Rui-Min Zhong (Food Chemistry, 2024)

Development of a PEI-coated SWNTs Nanocarrier for efficient delivery of CRISPR/Cas9 in early embryos of Litopenaeus vannamei - Jia L. Men; Yu T. Zhang; Yue B. Pei; Na Li; Jian H. Xiang; Hai L. Zhou (Aquaculture, 2024)

Critical Roles of Surface-Enhanced Heterogeneous Oxidation of SO2 in Haze Chemistry: Review of Extended Pathways for Complex Air Pollution - Zihao Zhang; Haiwei Li; Wingkei Ho; Long Cui; Qihui Men; Li Cao; Yunjiang Zhang; Junfeng Wang; Cheng Huang; Shun-cheng Lee; Yu Huang; Mindong Chen; et al. (Current Pollution Reports, 2024)

Fracture behavior of yellow sandstone under freeze–thaw cycles with varied saturation states: An investigation of mode I fracture - Tubing Yin; Jianfei Lu; Yang Yu; You Wu; Jihao Wang; Jiaqi Men (Geomechanics for Energy and the Environment, 2023)

Drug Dissolution in Oral Drug Absorption: Workshop Report - Kimberly Raines; Payal Agarwal; Patrick Augustijns; Alaadin Alayoubi; Lucas Attia; Annette Bauer-Brandl; Martin Brandl; Parnali Chatterjee; Hansong Chen; Yuly Chiang Yu; Carrie Coutant; Ana Luisa Coutinho; et al. (The AAPS Journal, 2023)
The in-person workshop “Drug Dissolution in Oral Drug Absorption” was held on May 23–24, 2023, in Baltimore, MD, USA. The workshop was organized into lectures and breakout sessions. Three common topics that were re-visited by various lecturers were amorphous solid dispersions (ASDs), dissolution/permeation interplay, and in vitro methods to predict in vivo biopharmaceutics performance and risk. Topics that repeatedly surfaced across breakout sessions were the following: (1) meaning and assessment of “dissolved drug,” particularly of poorly water soluble drug in colloidal environments ( e.g. , fed conditions, ASDs); (2) potential limitations of a test that employs sink conditions for a poorly water soluble drug; (3) non-compendial methods ( e.g. , two-stage or multi-stage method, dissolution/permeation methods); (4) non-compendial conditions ( e.g. , apex vessels, non-sink conditions); and (5) potential benefit of having both a quality control method for batch release and a biopredictive/biorelevant method for biowaiver or bridging scenarios. An identified obstacle to non-compendial methods is the uncertainty of global regulatory acceptance of such methods.

Enhanced denitrification of the AO-MBBR system used for expressway service area sewage treatment: A new perspective on decentralized wastewater treatment - Xin Xing; Xin Yuan; Yu Zhang; Cong Men; Zhuowei Zhang; Xiaoying Zheng; Dong Ni; Huatian Xi; Jiane Zuo (Journal of Environmental Management, 2023)

Impact of long-term operation of nuclear power plants on the marine ecosystem of Daya Bay - Yue Yu; Peng Zhou; Wu Men (Marine Pollution Bulletin, 2023)

Sex-specific effect of perfluoroalkyl substances exposure on liver and thyroid function biomarkers: A mixture approach - Ze Yang; Ruifang Liu; Hongbo Liu; Jiemin Wei; Xiaohui Lin; Mingyue Zhang; Yu Chen; Jingyun Zhang; Meiqing Sun; Zhe Feng; Jian Liu; Xiangyang Liu; et al. (International Journal of Hygiene and Environmental Health, 2023)

New insights into membrane fouling during direct membrane filtration of municipal wastewater and fouling control with mechanical strategies - Yu Men; Zifu Li; Lixin Zhu; Xuemei Wang; Shikun Cheng; Yaping Lyu (Science of The Total Environment, 2023)

Impacts of El Niño–Southern Oscillation on tropical precipitation via triggering anomaly water vapour transport from ocean to land - Jialin Wang; Feifei Pan; Haiyan Li; Pingli An; Guolin Han; Kang Jiang; Xiao Chen; Ziyuan Zhang; Yu Song; Na Huang; Shangqian Ma; Zhenzhen Zhang; et al. (International Journal of Climatology, 2023)
Atmospheric water vapour transport is one of the most active components of the hydrological cycle, which shows great effects on the regional climate variability, while it is largely affected by the large‐scale circulation systems. El Niño–Southern Oscillation (ENSO) shows a remarkable influence on the atmospheric water circulation via disrupting the normal/regular water vapour transport processes, producing the anomaly water vapour fluxes input from ocean to land ( Q net ), and leading to regional precipitation anomalies. However, their quantitative impact has not been fully studied. This study quantified the effect of ENSO on the water vapour transport from ocean to land and identified its impact on tropical precipitation anomalies. The results showed that the global detrended Q net displayed a significantly negative correlation with the strength of ENSO. The notable impact of ENSO on Q net was largely affected by the different patterns of the atmospheric moisture circulation during El Niño and La Niña and was responsible for the change of the spatial distribution of precipitation over the Tropics. El Niño reduced precipitation over the Malay Archipelago and increased precipitation over south China, especially in boreal winter, while La Niña enhanced precipitation over the Malay Archipelago. This study identified the impacts of ENSO on the circulation and water vapour transport process and improved our understanding of the influencing mechanism of ENSO on regional precipitation anomalies, which has important significance on regional water resource management and disaster risk assessment, especially as the extreme climate events have become increasingly frequent.

Benzimidazole fungicide biotransformation by comammox Nitrospira bacteria: Transformation pathways and associated proteomic responses - Ping Han; Ana B. Rios-Miguel; Xiufeng Tang; Yaochun Yu; Li-Jun Zhou; Lijun Hou; Min Liu; Dongyao Sun; Mike S.M. Jetten; Cornelia U. Welte; Yujie Men; Sebastian Lücker (Journal of Hazardous Materials, 2023)

Simultaneous recovery of nutrients and water from human urine by a novel thermally activated peroxydisulfate and membrane distillation integrated system - Yaping Lyu; Xiuwei Ao; Shikun Cheng; Nana Liu; Yu Men; Zifu Li (Chemical Engineering Journal, 2023)

Preparation of Chitosan Modified Cu-Metal–Organic Framework Antibacterial Microspheres and Their Application in Adsorption of Cr(VI) from Aqueous Solution - Yongfeng Kang; Yingyuan Yu; Bingqian Zhang; Jianning Fu; Xixi Jiang; Baiyun Jia; Xiaoling Men; Li Li (Water, Air, & Soil Pollution, 2023)

Association between exposure to perfluoroalkyl substances and uric acid in Chinese adults - Ze Yang; Kun Men; Jiaxin Guo; Ruifang Liu; Hongbo Liu; Jiemin Wei; Jingyun Zhang; Liangpo Liu; Xiaohui Lin; Mingyue Zhang; Yong Liu; Yu Chen; et al. (Chemosphere, 2023)

Dietary supplementation of two indigenous Bacillus spp on the intestinal morphology, intestinal immune barrier and intestinal microbial diversity of Rhynchocypris lagowskii - Xin-yu Lei; Dong-ming Zhang; Qiu-ju Wang; Gui-qin Wang; Yue-hong Li; Yu-rou Zhang; Men-nan Yu; Qi Yao; Yu-ke Chen; Zhi-xin Guo (Fish Physiology and Biochemistry, 2022)

Association of selenium, arsenic, and other trace elements in drinking water and urine in residents of the plateau region in China - Shuangmei Tong; Linsheng Yang; Hongqiang Gong; Li Wang; Hairong Li; Jiangping Yu; Yonghua Li; Yangzong Deji; Cangjue Nima; Shengcheng Zhao; Zongji Gesang; Chang Kong; et al. (Environmental Science and Pollution Research, 2022)

Stage correlation of symbiotic bacterial community and function in the development of litchi bugs (Hemiptera: Tessaratomidae) - Zhi-Hui Liu; Zi-Wen Yang; Jing Zhang; Jiu-Yang Luo; Yu Men; Yan-hui Wang; Qiang Xie (Antonie van Leeuwenhoek, 2022)

In-Situ Seawater Gamma Spectrometry with LaBr3 Detector at a Nuclear Power Plant Outlet - Daowei Dou; Zhi Zeng; Wen Yu; Ming Zeng; Wu Men; Feng Lin; Hao Ma; Jianping Cheng; Junli Li (Journal of Marine Science and Engineering, 2021)
In a nuclear emergency, the application of in situ spectrometers for monitoring environmental radioactivity is significantly important, as information on the type and activity of radionuclides released from the accident can be obtained quickly. However, in emergency environmental radiological monitoring, a balance between energy resolution and detecting efficiency must be considered in selecting an appropriate detector. In this study, in situ gamma spectrometry was conducted with the LaBr3 detector to determine the radioactivity of seawater at the discharging outlet of a coastal nuclear power plant in southeast China. The results show that the LaBr3 scintillator has excellent energy resolution and detection efficiency, making it a promising detector for emergency monitoring.

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

A mixture of chloromethylisothiazolinone and methylisothiazolinone impairs rat vascular smooth muscle by depleting thiols and thereby elevating cytosolic Zn2+ and generating reactive oxygen species - Van Quan Do; Yoon-Seok Seo; Jung-Min Park; Jieun Yu; Men Thi Hoai Duong; Junichi Nakai; Sang-Kyum Kim; Hee-Chul Ahn; Moo-Yeol Lee (Archives of Toxicology, 2021)

Enhancement of protoplast preparation and regeneration of Hirsutella sinensis based on process optimization - Li-Qun Jin; Zhe-Wen Xu; Xiao-Hui Men; Bo-Zhang; Zhi-Qiang Liu; Yu-Guo Zheng (Biotechnology Letters, 2020)

Baicalein exerts neuroprotective effect against ischaemic/reperfusion injury via alteration of NF-kB and LOX and AMPK/Nrf2 pathway - Yu Yuan; Weidong Men; Xiaosong Shan; Hexin Zhai; Xiaoxia Qiao; Lianting Geng; Chunhui Li (Inflammopharmacology, 2020)

Application of Adeno-Associated Virus Vectors for Engineering SCF-Containing Extracellular Vesicles of Mesenchymal Stromal Cells - E. S. Zubkova; I. B. Beloglazova; E. G. Evtushenko; A. T. Kopylov; E. K. Shevchenko; K. V. Dergilev; E. I. Ratner; E. V. Parfenova; M. Yu. Men’shikov (Bulletin of Experimental Biology and Medicine, 2019)

Combination of Mesenchymal Stromal Cells and Cardiac Stem Cells in a Multilayer Cell Construct Promotes Activation of Notch Signaling and Initiation of Endothelial Differentiation - E. K. Shevchenko; K. V. Dergilev; Z. I. Tsokolaeva; I. B. Beloglazova; Yu. D. Molokotina; E. V. Parfenova; M. Yu. Men’shikov (Bulletin of Experimental Biology and Medicine, 2019)

Modulation of the Inflammatory Status of Macrophages and Their Paracrine Effect on the Sensitivity of Adipocytes to Insulin with Sirtuin and PPARγ Receptor Activators - Yu. S. Stafeev; S. S. Michurina; E. S. Zubkova; I. B. Beloglazova; E. I. Ratner; E. V. Parfenova; M. Yu. Men’shikov (Bulletin of Experimental Biology and Medicine, 2018)

Insights into the roles of anammox bacteria in post-treatment of anaerobically-treated sewage - Qian Wang; Giin-Yu Amy Tan; Mohammad Azari; Xiaowu Huang; Martin Denecke; Yujie Men; Jin-Young Jung; Satoshi Okabe; Muhammad Ali; Yu-Tzu Huang; Zhuoying Wu; Wai-hung Lo; et al. (Critical Reviews in Environmental Science and Technology, 2018)

The function of OsbHLH068 is partially redundant with its homolog, AtbHLH112, in the regulation of the salt stress response but has opposite functions to control flowering in Arabidopsis - Hung-Chi Chen; Vicki Hsieh-Feng; Pei-Chun Liao; Wan-Hsing Cheng; Li-Yu Liu; Yun-Wei Yang; Ming-Hsin Lai; Men-Chi Chang (Plant Molecular Biology, 2017)

Non-viral and viral delivery systems for CRISPR-Cas9 technology in the biomedical field - Zhi-Yao He; Ke Men; Zhou Qin; Yang Yang; Ting Xu; Yu-Quan Wei (Science China Life Sciences, 2017)

Regulatory Effects of Urokinase on Mesenchymal Stromal Cell Migration, Proliferation, and Matrix Metalloproteinase Secretion - I. B. Beloglazova; E. S. Zubkova; Z. I. Tsokolaeva; Yu. S. Stafeev; K. V. Dergilev; E. I. Ratner; M. V. Shestakova; O. Yu. Sukhareva; E. V. Parfenova; M. Yu. Men’shikov (Bulletin of Experimental Biology and Medicine, 2016)

Chlorobenzene Destruction over Mesostructured CuO and MnO x Co-Modified CeO2 Catalyst: Activity and Activation Route - Chi He; Gaoshan Men; Yanke Yu; Hua Pan; Bitao Xu (Water, Air, & Soil Pollution, 2015)

Urokinase Stimulates Production of Matrix Metalloproteinase-9 in Fibroblasts with Involvement of Reactive Oxygen Species - E. S. Zubkova; M. Yu. Men’shikov; O. S. Plekhanova; I. B. Beloglazova; E. I. Ratner; E. V. Parfenova (Bulletin of Experimental Biology and Medicine, 2014)

Proteolytically Inactive Recombinant Forms of Urokinase Suppress Migration of Endothelial Cells - I. B. Beloglazova; E. S. Zubkova; D. V. Stambol’skii; O. S. Plekhanova; M. Yu. Men’shikov; Zh. A. Akopyan; R. Sh. Bibilashvili; E. V. Parfenova; V. A. Tkachuk (Bulletin of Experimental Biology and Medicine, 2014)

Contribution of SATB2 to the stronger osteogenic potential of bone marrow stromal cells from craniofacial bones - Ping Zhang; Jie Men; Yu Fu; Tengfei Shan; Jinhai Ye; Yunong Wu; Zhenjiang Tao; Laikui Liu; Hongbing Jiang (Cell and Tissue Research, 2012)

A preliminary study on the molecular evolution of the two routes of intrauterine transmission of HBV - H. Sun; X. Tang; B. Wang; J. Zhang; H. Cheng; H. Su; F. Li; K. Men; S. Wang; L. Zhao; J. Xu; X. Yu; et al. (Archives of Virology, 2012)

Erratum to: To the article “In Vitro Effect of Knotolan, a New Lignan from Abies sibirica, on the Growth of Hormone-Dependent Breast Cancer Cells” by O. S. Zhukova, L. V. Fetisova, A. V. Trishin, N. Yu. Anisimova, A. E. Shcherbakov, D. V. Yashunskii, D. E. Tsvetkov, V. M. Men’shov, M. V. Kiselevskii and N. E. Nifant’ev, Vol. 149, No. 4, pp. 511–514, October, 2010 - O. S. Zhukova; L. V. Fetisova; A. V. Trishin; N. Yu. Anisimova; A. M. Scherbakov; D. V. Yashunskii; D. E. Tsvetkov; V. M. Men’shov; M. V. Kiselevskii; N. E. Nifant’ev (Bulletin of Experimental Biology and Medicine, 2011)

In Vitro Effect of Knotolan, a New Lignan from Abies sibirica, on the Growth of Hormone-Dependent Breast Cancer Cells - O. S. Zhukova; L. V. Fetisova; A. V. Trishin; N. Yu. Anisimova; A. E. Shcherbakov; D. V. Yashunskii; D. E. Tsvetkov; V. M. Men’shov; M. V. Kiselevskii; N. E. Nifant’ev (Bulletin of Experimental Biology and Medicine, 2010)

Effects of the novel allelochemical ethyl 2-methylacetoacetate from the reed (Phragmitis australis Trin) on the growth of several common species of green algae - Yu-Jie Men; Hong-Ying Hu; Feng-Min Li (Journal of Applied Phycology, 2007)

Urokinase induces ROS production in vascular smooth muscle cells - O. S. Plekhanova; M. Yu. Men’shikov; P. P. Bashtrykov; B. S. Berk; V. A. Tkachuk; E. V. Parfenova (Bulletin of Experimental Biology and Medicine, 2006)

Urokinase Increases the Content and Activity of Matrix Metalloproteinases 2 and 9 during in Vivo Constrictive Arterial Remodeling - M. A. Solomatina; O. S. Plekhanova; M. Yu. Men’shikova; E. I. Ratner; V. A. Tkachuk; E. V. Parfenova (Bulletin of Experimental Biology and Medicine, 2005)

Detection of antibodies to opioid and glutamate receptors by latex agglutination and enzyme immunoassay - A. V. Kharitonova; A. Yu. Men’shikova; T. G. Evseeva; N. A. Chekina; E. R. Bychkov; D. I. Skulyabin; S. A. Dambinova (Bulletin of Experimental Biology and Medicine, 2005)

Effect of recombinant forms of urokinase plasminogen activator on platelet aggregation and intracellular calcium accumulation - A. V. Zubkov; T. L. Bushueva; M. M. Minashkin; Ya. G. Gurskii; M. Yu. Men'shikov (Bulletin of Experimental Biology and Medicine, 1999)

Serotonin-induced platelet aggregation and release of3H-serotonin in patients with migraine - T. G. Pukhal'skaya; O. A. Kolosova; M. Yu. Men'shikov (Bulletin of Experimental Biology and Medicine, 1998)

Influence of fibrinolysis system on ADP- and serotonin-induced aggregation of human platelets - M. Yu. Men'shikov (Bulletin of Experimental Biology and Medicine, 1998)